The Status of Children Born Out of Wedlock in Constitutional Court Ruling No. 46/PUU-VIII/2010: A Maqasid Analysis by Jasser Auda - Herpagus Herpagus; Syukri Syukri; Moh. Asyiq Amrulloh (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyze the status of children born out of wedlock as addressed in Constitutional Court Decision Number 46/PUU-VIII/2010 and to evaluate the decision's alignment with the principles of maqasid al-shari'ah through the lens of the systems theory developed by Jasser Auda. This research employs a library research methodology with a normative-juridical approach. Primary data sources include Constitutional Court Decision No. 46/PUU-VIII/2010 and Jasser Auda’s works on maqasid al-shari'ah, while secondary data were gathered from relevant books, journals, articles, and research findings. Data analysis utilized the content analysis method, applying Jasser Auda’s six system features as the analytical framework: cognitive nature, wholeness, openness, interconnectedness, multi-dimensionality, and meaningfulness. The study finds that Constitutional Court Decision No. 46/PUU-VIII/2010 represents a progressive legal ruling that breaks away from the positivist-legalistic paradigm in marriage law. Based on the analysis using Jasser Auda’s six system features, the decision satisfies all maqasid al-shari'ah criteria: (1) it is grounded in the concept of istilhaq within Islamic law; (2) it provides protection and justice for children born out of wedlock; (3) it is responsive to changing times and avoids entrapment in binary classifications; (4) it considers maqasid 'ammah (general), khassah (specific), and juz'iyyah (partial) objectives; (5) it transcends binary opposition paradigms; and (6) it restores the objective of Islamic law to the public interest (maslaha). This research offers theoretical contributions to the development of contemporary Islamic law and provides practical insights for legal practitioners, policymakers, and legislators in formulating regulations that protect the rights of children born out of wedlock without conflicting with religious principles.